(3QSGdI aj GdQVGYs - (3GdcQcj GdYGedj, CHh GdMSf, GdeMbb GdKGfj, GdeMbb GdKGfj, Ydj Hf GdMSjf Hf YHO GdYGdj GdcQcj GdYGedj, J (B940(3g` (B1534(3es ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg ceG gh Ggdg (B... (3GYde habc Gddg Cfg bO GTJgQ Ydi CdSfI GdWdHI aj gPG GdYUQ JMQje GdeQCI Ydi RhLgG HGQVGY ef SfPcQg hdG jYQahf aj Pdc GUdGs
(3BNQgG (B:s
(3BNQgG(B: (3Hd jefY GdJdGRe CUdG aEf KHhJ HfhI TNU dBNQ jbJVj KHhJ GdCNhI dChdGOg dG HKhJ GdCNhI dCNhI ChdGOg hPdc ebJVi GdJMQje (B... (3agPG iNQ eG CQOfG LeYg hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L(B4: 281s
(3GdPQjYI, L (B11: 138s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis